2013
DOI: 10.1039/c3ee24429f
|View full text |Cite
|
Sign up to set email alerts
|

How to produce biodiesel easily using a green biocatalytic approach in sponge-like ionic liquids

Abstract: Hydrophobic ionic liquids (ILs) based on cations with long alkyl side-chains (e.g. N-octadecyl-N 0 ,N 00 ,N 000trimethylammonium bis(trifluoromethylsulfonyl)imide ([C 18 tma][NTf 2 ])) are switchable ionic liquid/solid phases with temperature that behave as sponges. As liquid phases, they are excellent monophasic reaction media for lipase-catalyzed methanolysis of triolein, resulting in fast and efficient biodiesel synthesis, e.g. up to 100% yield in 8 h at 60 C, with exceptional enzyme stability (up to 1370 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…37b Other authors reported how 1alkyl-3-methylimidazolium ILs (e.g. 30 The IL net could be considered as a nano-sponge with holes of variable volume, which are suitable for housing or releasing hydrophobic molecules as a function of their liquid or solid phase, respectively. 37c Ohno and co-workers reported several interesting poly(IL)s showing temperature-dependent phase behaviour after mixing with pure water, and also with aqueous salts solutions.…”
Section: From Structure To Application As Sponge-like Ionic Liquidsmentioning
confidence: 99%
“…37b Other authors reported how 1alkyl-3-methylimidazolium ILs (e.g. 30 The IL net could be considered as a nano-sponge with holes of variable volume, which are suitable for housing or releasing hydrophobic molecules as a function of their liquid or solid phase, respectively. 37c Ohno and co-workers reported several interesting poly(IL)s showing temperature-dependent phase behaviour after mixing with pure water, and also with aqueous salts solutions.…”
Section: From Structure To Application As Sponge-like Ionic Liquidsmentioning
confidence: 99%
“…Reaction yield estimated by Raman spectroscopy for the transesterification of soybean oil by methanol using 10 wt.% of the enzyme pseudomonas cepacia at 40°C using C 8 C 1 ImTFSI (#) or C 10 C 1 ImTFSI (Ã). For comparison, reaction rates observed by other authors are also shown, while using: C 12 C 1 ImTFSI and 10 wt.% of the enzyme candida antarctica at 60°C (blue, reproduced from reference [25]); C 16 C 1 ImTFSI and 10 wt.% of the enzyme candida antarctica at 60°C (red, reproduced from reference [26]); C 4 tmaTFSI and 18 wt.% of the enzyme candida antarctica at 60°C (green, reproduced from reference [27]); C 8 C 1 Im:TFSI and 2 wt.% of the enzyme candida antarctica at 50°C (yellow, reproduced from reference [21]); C 4 C 1 ImTFSI and 20 wt.% of the enzyme pseudomonas cepacia at room temperature (violet, reproduced from reference [5]), and a Brønsted acidic ionic liquid for increasing temperatures between 80 and 160°C (gray, reproduced with permission from reference [19]). (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Effect Of the Alkyl Chain Lengthmentioning
confidence: 88%
“…SI-3. The benefits of long alkyl chains have recently been observed by Lozano et al [27] when substituting the butyl (n = 4) chain with a dodecyl (n = 12) in ammonium based ionic liquids. The same authors have also reported that when varying the chain length from decyl (n = 10) to octodecyl (n = 18) in imidazolium based ionic liquids the reaction yield varied only slightly [26].…”
Section: Effect Of the Alkyl Chain Lengthmentioning
confidence: 90%
See 2 more Smart Citations